Upregulated bone morphogenetic protein 8A (BMP8A) in triple negative breast cancer (TNBC) and its involvement in the bone metastasis - Sui, Laijian; Cong, Yizi; Liu, Ming; Liu, Xiangyi; Xu, Yali; Jiang, Wen G.; Ye, Lin (Frontiers in Cell and Developmental Biology, 2024)
Objective The present study aimed to investigate the involvement of aberrant BMP8A expression in TNBC and bone metastasis. Methods Aberrant expression of BMP8A in breast cancer was first determined by analyzing The Cancer Genome Atlas breast cancer cohort (TCGA-BRCA) and an immunohistochemical (IHC) staining of BMP8A in a breast cancer tissue microarray (TMA). Clinical relevance of deregulated BMP8A in breast cancer was assessed using Kaplan-Meier online analysis. The influence of BMP8A on cellular functions of two TNBC cell lines was assessed using in vitro assays. Conditional medium (CM) collected from the supernatant of hFOB cells and bone matrix extract (BME) was applied to mimic the bone micro-environment to evaluate the role played by BMP8A in bone metastasis. Correlations with both osteolytic and osteoblastic markers were evaluated in the TCGA-BRCA cohort. Expression of certain responsive genes was quantified in the BMP8A overexpression cell lines. Additionally, signal transduction through both Smad-dependent and independent pathways was evaluated using Western blot assay. Results Compared to the adjacent normal tissues, BMP8A expression was significantly increased in primary tumors (p < 0.05) which was associated with shorter distant metastasis free survival (DMFS) in TNBC (p < 0.05). BMP8A was observed to enhance cell invasion and migration within TNBC cells. In the simulated bone milieu, both MDA-MB-231BMP8Aexp and BT549BMP8Aexp cells presented enhanced invasiveness. BMP8A level was strongly correlated with most osteolytic and osteoblastic markers, suggesting the potential involvement of BMP8A in bone metastasis in TNBC. Receptor activator of nuclear factor kappa-B ligand (RANKL) expression was significantly increased in BMP8A overexpressed triple-negative cell lines (MDA-MB-231 and BT549). Furthermore, enhanced phosphorylation of Smad3 and increased expression of epidermal growth factor receptor (EGFR) were observed in MDA-MB-231 cells overexpressing BMP8A. Conclusion BMP8A was upregulated in TNBC which was associated with poorer DMFS. BMP8A overexpression enhanced the invasion and migration of TNBC cells. With a putative role in osteolytic bone metastasis in TNBC, BMP8A represents a promising candidate for further investigation into its therapeutic potential.